1986
DOI: 10.3406/bulmi.1986.7924
|View full text |Cite
|
Sign up to set email alerts
|

Polytype formation and transformation during the reaction-bonding of silicon carbide

Abstract: This paper explores the polytype distribution and polytypic transformations occurring during the reaction-bonding of a commercial silicon carbide, REFEL. The initially formed polytype is found to be almost exclusively β-SiC, which either deposits epitaxially on the original α-SiC grits or as fine material, in situ in the silicon. The exothermic nature of the reaction causes the epitaxially deposited material to undergo the β→α solid state transformation, usually going almost to completion in a few minutes. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Our results show that the 6H-SiC phase is the ground state phase with the lowest total energy. This is in agreement with experiments [2,33,46], which indicate that 6H-SiC is the stable phase at high temperatures and probably 4H-SiC is stable at low temperatures. Polytypic transformation of 4H-SiC into 6H-SiC has been observed experimentally [47,48].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show that the 6H-SiC phase is the ground state phase with the lowest total energy. This is in agreement with experiments [2,33,46], which indicate that 6H-SiC is the stable phase at high temperatures and probably 4H-SiC is stable at low temperatures. Polytypic transformation of 4H-SiC into 6H-SiC has been observed experimentally [47,48].…”
Section: Discussionsupporting
confidence: 92%
“…These results seem to suggest that the 3C-SiC phase is never the stable structure at any temperature. However experiments [2,[33][34][35][36] found that the 3C-SiC phase does prefer to grow epitaxially. A good model that Heine et al [12] have introduced can explain the experimental phenomenon.…”
Section: Introductionmentioning
confidence: 99%